2005
DOI: 10.1590/s0100-29452005000100026
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas semilenhosas de lichieira utilizando ácido indolbutírico

Abstract: O objetivo deste trabalho foi estudar o enraizamento de estacas semilenhosas de lichieira ( Litchi chinensis Sonn.) da cultivar Bengal, empregando ácido indolbutírico (AIB) e sistema de nebulização intermitente. As estacas apicais foram coletadas nos meses de outubro (Primavera), janeiro (Verão) e abril (Outono), acondicionadas adequadamente e transferidas para uma estufa com nebulização intermitente, onde receberam as aplicações de : 0; 1.000; 2.000; 3.000 e 4.000 mg L-1 de AIB, com imersão da base das estaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 2 publications
(2 reference statements)
3
6
0
8
Order By: Relevance
“…These results corroborate those obtained by Carvalho et al (2005), who did not observe the influence of IBA application in the concentrations of 0 to 4000 mg L -1 in 'Bengal' lychee cuttings, for the same cultivar evaluated in the present study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results corroborate those obtained by Carvalho et al (2005), who did not observe the influence of IBA application in the concentrations of 0 to 4000 mg L -1 in 'Bengal' lychee cuttings, for the same cultivar evaluated in the present study.…”
Section: Resultssupporting
confidence: 93%
“…Contrasting results were described by Koyama et al (2014), however, these authors collected cuttings at another season (winter), which can had influenced these results. Carvalho et al (2005) observed that the greatest number, length, fresh and dry mass of roots of 'Bengal' lychee cuttings was obtained in cuttings collected in the spring, regardless of the AIB concentrations tested. On the other hand, the same authors obtained a higher percentage of rooted cuttings when cuttings were collected in the summer (48.7%), followed by spring (24.5%) and autumn (8.1%).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…De acordo com Dias et al (2012a), o uso de material juvenil, como miniestacas, pode dispensar a aplicação de hormônio exógeno, pois esse material apresenta balanço hormonal endógeno favorável ao enraizamento. Para espécies florestais, o uso de hormônio exógeno tem como finalidade aumentar o número de raízes por miniestacas, além de acelerar sua formação e uniformizar o enraizamento (CARVALHO et al, 2005). Assim, esse hormônio pode ser dispensado ou utilizado em baixíssimas concentrações (XAVIER; WENDLING; SILVA, 2009).…”
Section: Resultsunclassified
“…A cultivar Bengal é uma das mais comercializadas. A árvore é de grande vigor e produtiva, mas requer boas condições de temperatura, umidade do solo e nutrição durante a fase de crescimento dos frutos (Carvalho et al, 2005). Os frutos são cordiformes, com peso médio de 21 g, coloração vermelho-brilhante, polpa firme, semente grande e com cerca de 20-35% de abortos dos frutos.…”
unclassified